From Concept to Concrete: Digital Twins Enabling Different Levels of Lean Construction - Owais, Omar; Poshdar, Mani; Bidhendi, Ali; Jafar, Kamal; Sarhan, Saad (IGLC, 2024)
The integration of Digital Twins (DTs) in Lean Construction (LC) represents a transformative approach to enhance collaboration, efficiency, waste reduction, and decision-making in construction projects. This paper explores the potential of DTs across different levels of LC through a comparative analysis method, aiming to establish a robust implementation foundation for lean organisations. Firstly, at the philosophy level, DTs foster collaboration, transparency, and respect for people by providing real-time data and virtual representations. They enable value maximisation, waste minimisation, and continuous improvement through visualisation, simulation, and data-driven decision-making. Besides, continuous improvement through monitoring and feedback loop. Secondly, at the principles level, DTs align closely with key LC principles such as value maximisation, continuous improvement, waste elimination, pull planning, continuous flow, and fast switch-over. By optimising processes, enhancing monitoring capabilities, and facilitating collaboration, DTs contribute to efficient project delivery. Thirdly, at the methods level, DTs complement LC methods such as Error Proofing, Value Stream Mapping, Target Value Design, and Last Planner System by facilitating real-time collaboration, visualising workflows, engaging stakeholders early, and providing error prevention capabilities. Overall, the strategic integration of DTs and LC thinking leads to improved project efficiency and value delivery, fostering ongoing innovation and improvement in the construction sector.